Penetapan Limit of Detection (LOD) dan Sensitivitas Metode Deteksi Pseudomonas aeruginosa dalam Berbagai Matriks Sediaan Obat - Nur Aini; Maria Purba; Sitoresmi Triwibowo; Nenden Sholihatul; Ratna Wulandari (Badan Pengawas Obat dan Makanan, 2021)
Contamination of certain microorganisms in pharmaceutical products can potentially reduce or even inactivate therapeutic activity and harm patient health. Pharmacopoeia monograph determine the microbiological quality in medicinal products. One of them is P. aeruginosa parameters which should not be present in pharmaceutical preparations. Pharmacopoeia states that microbial detection methods must be able to detect microorganisms, including P.aeruginosa not more than 100 colonies, but the actual detection limit has never been set quantitatively and many variables can affect the microorganism recovery. This study aims to determine the range of Limit of Detection (LOD) values and the sensitivity of the P. aeruginosa method on pharmaceutical products. Detection method of P. aeruginosa refers to the specific microbial test of the Indonesian Pharmacopoeia VI (2020) is culture media methods. Experiments used eight pharmaceutical products representing five dosage forms contaminated with P. aeruginosa ATCC 9027 with three levels of concentration. The results determined LOD range and sensitivity of P. aeruginosa detection method in pharmaceutical products, and analyzed descriptively. This study shows that pharmacopeia method of P. aeruginosa testing can detect P. aeruginosa in various drug preparation matrices with a detection limit of 1-10 colonies and a sensitivity of 100%. Results of this study can be used as reference for LOD value in the verification of the P. aeruginosa detection in medicinal product.